Author Correction: Anti-trypanosomatid drug discovery: an ongoing challenge and a continuing need. Issue 11 (November 2018) - Field, Mark; Horn, David; Fairlamb, Alan; Ferguson, Michael; Gray, David; Read, Kevin; Rycker, Manu; Torrie, Leah; Wyatt, Paul; Wyllie, Susan; Gilbert, Ian
The structures of nifurtimox in Table 1 were incorrect and have been updated in the pdf and online. The authors apologize for any confusion caused.